Heat-Technical Characteristics of Heat Pump Device for Heat Supply Systems - O.S.Komilov; S.S.Sayfulloev (Genius Journals, 2022)
This article analyzes the main energy parameters of steam-compressor heat pumps. In this case, the process of dependence of the heating coefficient of the heat pump on the boiling and condensing temperature of the refrigerant is studied and graphs are given. In addition, as a result of exergetic analysis of heat pumps analyzed the state of exergetic efficiency in creating a comfortable environment with high efficiency in the building
Keywords: heat pump; energy balance; heating coefficient; compressor